1983
DOI: 10.1111/j.1600-0676.1983.tb00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Low therapeutic value of D‐penicillamine in a short‐term prospective trial in primary biliary cirrhosis

Abstract: A small double-blind controlled trial to evaluate the short-term effects of D-penicillamine therapy was carried out in 24 patients with primary biliary cirrhosis (PBC). The daily dose of D-penicillamine was increased monthly by 250 mg until a total of 1 g daily was reached. Two out of 11 patients (18%) were withdrawn because of side-effects, as also were 4 out of 13 (31%) patients receiving the placebo. Transient improvement in symptoms was observed in 4of 11 patients on D-penicillamine, but also in 5 of 13 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The trial publication with most completed data were regarded as the primary reference, from which data were extracted. Six trials compared d ‐penicillamine vs. placebo/no intervention 8, 9, 21–24 . Bodenheimer et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trial publication with most completed data were regarded as the primary reference, from which data were extracted. Six trials compared d ‐penicillamine vs. placebo/no intervention 8, 9, 21–24 . Bodenheimer et al .…”
Section: Resultsmentioning
confidence: 99%
“…No trials reported sample size estimation. Five trials reported the number of dropouts in d ‐penicillamine (74 patients) and in control group (16 patients), respectively 9, 21–24 . Bodenheimer et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though an ATP7B heterozygote could be affected by secondary copper toxicosis of primary biliary cirrhosis, the treatment of choice should be ursodeoxycholic acid rather than penicillamine. 29,30 In conclusion, although the number of patients studied was small, the internationally proposed system could be considered fairly reliable for screening Japanese patients with WD. Long-range PCR was recommended for screening because there were patients with gross deletions involving more than one exon in the ATP7B gene.…”
Section: Discussionmentioning
confidence: 86%
“…A carrier state of HCV in a heterozygous member of the WD family was successfully treated with anti‐HCV agents (case 14). Even though an ATP7B heterozygote could be affected by secondary copper toxicosis of primary biliary cirrhosis, the treatment of choice should be ursodeoxycholic acid rather than penicillamine 29,30 …”
Section: Discussionmentioning
confidence: 99%